Mystical features of Christianity in Persian poetry - Qasim Muhammad, Nazik; Ali Majid, Rana (Al-Adab Journal, 2020)
Religious poems are one of the well-known literary genres who poets began to benefit from its symbolic elements & contents in order to show and clarify their nice and beautiful poetic meanings. Christianity and the life of Jesus are one of the clear example that have been placed before the ascetics and Christian clergy in general and Iranian in particular.Jesus Christ is a figure who has occupied a prominent position since ancient times, his name and remembrance are present in the mind of every human being. The Christ in Iranian culture is a symbol of freedom, purity and honesty for this reason, these people have painted in their mind a pleasant and likeable image of him.The Iranian vision of the Christ's prophets arised in the first place by mentioning the signals and several and repeated hints of the Holy Quran to the holiness and purity of the Christian family.Most writers and poets of Persian literature have used the name of Christ and Christian religious terms widely through Islamic teachings (Holy Quran) to showed that in their poems as a novel and not as a rule so that they did not go in this way without evidence.In this research, we showed how Iranian poets are influenced by Christianity and its religion terms as well as showed the references some of the meanings and contents common in this regard in their poems.